2011
DOI: 10.1186/1751-0147-53-48
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced bacterial immunogens in the gastrointestinal tract of dairy cows: Impacts on immunity and metabolism

Abstract: Dairy cows are often fed high grain diets to meet the energy demand for high milk production or simply due to a lack of forages at times. As a result, ruminal acidosis, especially subacute ruminal acidosis (SARA), occurs frequently in practical dairy production. When SARA occurs, bacterial endotoxin (or lipopolysaccharide, LPS) is released in the rumen and the large intestine in a large amount. Many other bacterial immunogens may also be released in the digestive tract following feeding dairy cows diets contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 49 publications
(81 reference statements)
4
93
0
Order By: Relevance
“…As a consequence, the ruminant microbial ecology and systemic metabolic state will change because of the rapid fermentation and subsequent excessive organic acids accumulation, and such animals are likely to suffer metabolic disorders such as acidosis, fatty liver, laminitis and even systemic inflammation (Alegre et al, 1988;Kleen et al, 2003;Plaizier et al, 2008;Dong et al, 2011;Tao et al, 2014). Our previous studies also showed that long-term feeding of a 65% high concentrate (HC) diet to lactating dairy goats led to subacute ruminal acidosis (SARA) and disruptions of mucosal barrier in the hindgut (Dong et al, 2013;Tao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the ruminant microbial ecology and systemic metabolic state will change because of the rapid fermentation and subsequent excessive organic acids accumulation, and such animals are likely to suffer metabolic disorders such as acidosis, fatty liver, laminitis and even systemic inflammation (Alegre et al, 1988;Kleen et al, 2003;Plaizier et al, 2008;Dong et al, 2011;Tao et al, 2014). Our previous studies also showed that long-term feeding of a 65% high concentrate (HC) diet to lactating dairy goats led to subacute ruminal acidosis (SARA) and disruptions of mucosal barrier in the hindgut (Dong et al, 2013;Tao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that high grain diets will result in increased release of LPS in the rumen as well as in the intestine (Gozho et al 2006;Khafipour et al 2009;Plaizier et al 2009;Dong et al 2011;Plaizier et al 2012). A recent study by Steele et al (2011) showed that the structural integrity of the rumen epithelium was compromised during high grain feeding, which can result in translocation of LPS into the circulation across the rumen epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…When cattle are fed high-concentrate diets, ruminal acidosis, especially subacute ruminal acidosis (SARA), may occur in practical beef production. As a result, the harmful and toxic substances, such as lactate (particularly the D-isomer), ethanol, histamine, tyramine, tryptamine, and bacterial endotoxin (or lipopolysaccharide, LPS), are released in the rumen in a large amount (Dong et al 2011). Among those substances, LPS has received a lot of attention because it potentially causes systemic immune responses and metabolic changes in the body Dong et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations